2021
DOI: 10.21203/rs.3.rs-129041/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The gut hormone Allatostatin C/Somatostatin regulates food intake and metabolic homeostasis under nutrient stress

Abstract: The intestine is a central regulator of metabolic homeostasis. Dietary inputs are absorbed through the gut, which senses their nutritional value and relays hormonal information to other organs to coordinate systemic energy balance. However, the specific gut hormones that communicate energy availability to target organs to induce appropriate metabolic and behavioral responses are poorly defined. Here we show that the enteroendocrine cells (EECs) of the Drosophila gut sense nutrient stress via the intracellular … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 39 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…2014; K amareddine et al . 2018a), AstC (K ubrak et al . 2022), and Crz (K ubrak et al 2016), have been shown to alter whole-body metabolism (Z hou et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2014; K amareddine et al . 2018a), AstC (K ubrak et al . 2022), and Crz (K ubrak et al 2016), have been shown to alter whole-body metabolism (Z hou et al .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a direct gut-to-brain signaling role has been shown for NPF, AstC and Dh31 in the context of nutrient regulation of feeding and metabolism (Y oshinari et al . 2021; K ubrak et al . 2022; L in et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary sugars positively regulate production and secretion of NPF from the gut EECs, whereas AstC secretion is induced by nutrient restriction ( Figure 3c ). Although both the NPF receptor (NPFR) and AstC receptor 2 (AstC-R2) are expressed in the CC, NPF and AstC have an inhibitory and facilitatory effect on secretion of Akh, respectively [ 186 , 187 ] ( Figure 3c ). NPFR is also expressed in the brain IPCs, where it facilitates secretion of Dilps [ 186 ] ( Figure 3c ).…”
Section: Gut-derived Peptide Hormones: Feeding and Energy Metabolismmentioning
confidence: 99%
“…EEC-derived NPF and AstC also directly act on the CC to regulate secretion of Akh [ 186 , 187 ] ( Figure 3c ). Dietary sugars positively regulate production and secretion of NPF from the gut EECs, whereas AstC secretion is induced by nutrient restriction ( Figure 3c ).…”
Section: Gut-derived Peptide Hormones: Feeding and Energy Metabolismmentioning
confidence: 99%